À propos du difficile chemin vers soi-même dans quelques romans de Jean-Philippe Toussaint - Zbierska-Mościcka, Judyta (Studia Romanica Posnaniensia, 2011)
Referring to anthropological reflections of Marc Augé and his proposed notions of supermodernity and non-places, the article discusses the identity of a contemporary man presented by examples of key novels by a Belgian writer, Jean-Philippe Toussaint (La Salle de bain, Monsieur, L’appareil-photo, La réticence, La télévision, Fuir, La vérité sur Marie). Toussaint’s characters are actually in a struggle against problems defined by Augé: lack of one’s own place, time for reflection and, mainly, a need for another human being.